White Matter Hyperintensity in Elderly Patients with Diabetes Mellitus Is Associated with Cognitive Impairment, Functional Disability, and a High Glycoalbumin/Glycohemoglobin Ratio - Tamura, Yoshiaki; Kimbara, Yoshiyuki; Yamaoka, Takuya; Sato, Ken; Tsuboi, Yuki; Kodera, Remi; Chiba, Yuko; Mori, Seijiro; Fujiwara, Yoshinori; Tokumaru, Aya M.; Ito, Hideki; Sakurai, Takashi; et al. (Frontiers in Aging Neuroscience, 2017)
Aims Although evidence has accumulated that white matter hyperintensity (WMH) is associated with the deterioration of cognitive function and impairment of activities of daily living (ADL), the clinical relevance of WMH in elderly patients with diabetes mellitus is not still clear. The aim of this study was to examine whether WMH volume is associated with ADL and cognitive function and whether glucose control and glucose variability can affect WMH volume in these patients. Methods This cross-sectional study investigated the associations of WMH with cognitive function and instrumental ADL (IADL), as well as metabolic and vascular risk factors in a total of 178 elderly patients with diabetes. The study assessed WMH volumes and the functional status of cognition and IADL. WMH volumes were evaluated by obtaining axial T2-weighted and fluid-attenuated inversion recovery sequence images on brain magnetic resonance imaging and assessing the images using Software for Neuro-Image Processing in Experimental Research. Results We found a significant association between WMH volumes and Mini-Mental State Examination (MMSE) scores (p = 0.039) and between WMH and IADL status (p = 0.006). Furthermore, we found significant relations of large WMH volumes with a high glycoalbumin/glycohemoglobin ratio (GA/HbA1c) (p < 0.001). Large WMH volumes were also found to be associated with a low body mass index (p = 0.014) and a low diastolic blood pressure (p = 0.024), but not with HbA1c. Multiple regression analysis showed that high GA/HbA1c, which reflects high glucose variability, was a significant determining factor for large WMH volumes. We also found that GA/HbA1c was negatively associated with both MMSE (p = 0.036) and IADL (p < 0.001). Conclusions GA/HbA1c, which is a marker of glucose variability, was independently associated with WMH volumes, which could lead to the decline of cognition and IADL in elderly patients with diabetes mellitus.